Left atrial strain is associated with left ventricular remodeling in patients with ST-elevation myocardial infarction. (25th November 2020) - Legallois, D; Hodzic, A; Milliez, P; Manrique, A; Saloux, E; Beygui, F
Abstract: Background/Introduction: Left ventricular remodeling (LVR) remains common and is associated with outcomes in patients with ST-elevation myocardial infarction (STEMI). Left atrial (LA) volume has been described as a predictor of outcomes in the latter population. Purpose: To investigate the association between LA mechanical function using speckle tracking imaging and LVR at follow-up in STEMI patients. Methods: Baseline 3D transthoracic echocardiograms were performed in 121 STEMI patients. LA global longitudinal strain was reported separately for the reservoir (LASr), conduit (LAScd), and contraction (LASct) phases. Follow-up echocardiograms were performed at 6 months. Results: Mean age was 58.3±12.5 years and 98 (81%) were men. Baseline left ventricular ejection fraction (LVEF) was 46.8% [41.0, 52.9] and significantly improved to 52.1% [45.8, 57.0] at follow-up, (p<0.001). A lower LASct was associated with a significant dilation of left ventricle at follow-up (%end-diastolic volume increase: −1.9% [−11.0, 15.2] in the two higher LASct tertiles group vs. 19.2% [5.0, 34.3] in the lower LASct tertile group, p=0.001). A higher %end-systolic volume increase at follow-up was associated with lower LASct as well: 12.6% [−16.2, 39.8] in the lower LASct group vs. −6.8% [−23.6, 14.4] in the two higher LASct tertiles group (p=0.004). Regarding LVEF, a low LVEF at follow-up was associated with the worst tertile of all LA strains (LASr, p=0.002; LAScd, p=0.01 and LASct, p=0.01). Conclusion(s): The three components of baseline LA strain were associated with LVEF at follow-up in patients with STEMI. Some of these components were also significantly associated with lower LVEF at baseline or predictive of a significant increase in left ventricular volumes during follow-up, indicating LVR. Funding Acknowledgement: Type of funding source: None